BUDGET MANAGEMENT ANALYSIS LOCAL AREA NETWORK INSTALLATION NETWORK (LAN) IN PT. JAKARTA METROPOLAR - Eka Agus Suharlan; Ir. Fitri Sjafrina, MMSI (Jurnal Sistem Informasi, 2000)
PT. JAKARTA METROPOLAR is one of the many companies engaged in the fieldof network installation services, particularly network Local Area Network (LAN).Network facilities owned by the company is a facilities LAN networking standardthat many companies are owned by the network usage. Constraints faced at themoment and yet there is determination on the company's articles of association of thenetwork installation of a Local Area Network (LAN) with the condition is less thanthe standard price which is owned by the marketing department.Solving problems that will put forward the writer, using the principal discussion inthe Budget Management application software supported by Microsoft Access.Expected to readers and entrepreneurs engaged in rental services Computer able tomake a LAN network installation budget and its installation.